New Directions in Restorative Justice - Elliott, Elizabeth; Gordon, Robert (Willan, 2013)
This book addresses a number of key themes and developments in restorative justice, and is based on papers originally presented at the 6th International Conference on Restorative Justice in Vancouver. It is concerned with several new areas of practice within restorative justice, with sections on restorative justice and youth, aboriginal justice and restorative justice, victimization and restorative justice, and evaluating restorative justice. Contributors to the book are drawn from leading experts in the field from the UK, US, Europe, Canada, Australia and New Zealand.